Natural Vermiculite Enables High‐Performance in Lithium–Sulfur Batteries via Electrical Double Layer Effects. (9th May 2019) - Wu, Feixiang; Lv, Haifeng; Chen, Shuangqiang; Lorger, Simon; Srot, Vesna; Oschatz, Martin; van Aken, Peter A.; Wu, Xiaojun; Maier, Joachim; Yu, Yan
Abstract: Lithium–sulfur batteries with potentially high specific energy are viewed as very promising candidates for next‐generation lightweight and low‐cost rechargeable batteries. However, sulfur‐based cathodes suffer from dissolution of polysulfides causing shuttle effects. Here, in order to confine elemental sulfur and anchor the polysulfides, a novel host that is an inexpensive natural clay mineral, viz., vermiculite is proposed. When compared to regular carbon–sulfur composites, vermiculite–sulfur composites offer promising rate capability and much better cycling stabilities, displaying capacity retentions of ≈89 and ≈93% within 200 cycles at C/2 and 1 C, respectively, and ≈60 % at C/5 within 1000 cycles. Postmortem studies, advanced adsorption tests, density functional theory calculations, and zeta potential measurements in combination with intrinsic characteristics of the natural vermiculite provide insights into the new mechanism. The vermiculite contains naturally present surface cations which show a strong tendency to adsorb S n 2− anions, hence protecting them from dissolution. The excess surface charge is most probably compensated by excess Li + in the space charge zones which is beneficial for charge transfer and local conductivity. The reported results show that natural clay‐minerals are promising sulfur hosts being able to fixate sulfides via electrical double layer effects, thus enabling high‐performance in lithium–chalcogen batteries. Abstract : Natural expanded‐vermiculite is reported as a promising sulfur host for achieving high‐performance lithium–sulfur batteries via electrical double layer effects. Due to the interactions between naturally present surface cations on vermiculite surface and polysulfides anions, the layer containing S n 2− anions are adsorbed on the vermiculite surface, which successfully reduce the polysulfide dissolution and their shuttle effects.